Interference between verbal concept formation and spatial mental rotation in female subjects - MAKANY, Tamas (Institutional Knowledge at Singapore Management University, 2002)
In this study the relation between spatial cognition and verbal intelligence abilities was examined in case of 52 women. Interference between mental rotation performance and verbal intelligence scores was found. Women with good verbal abilities have lower scores in mental rotation tasks than subjects with poorer verbal abilities. This finding is in accordance with some basic models of a dual-coding system. The spatial functions represented in mental rotation interfered with verbal-based concept formation and lexical knowledge in college women.